PEMETAAN INTENSITAS POLUSI PADA ISOLATOR JARINGAN TRANSMISI - Lanto Mohamad Kamil Amali (Foristek, 2011)
The problem in this study were: (1) how the intensity of pollution sector in the region polluted insulator, (2) how polluted insulator surface conductivity Parent substations in each region, (3) how to profile an appropriate insulators forsubstations with different levels of intensity of pollution sector in the region. To solve this problem pollutant samplingconducted on ceramic insulators on the channel milestone substation switchyard each region at two different points, namelyat the top of the insulator and the bottom fin insulators. The results showed the intensity of pollution for every region ofsubstation at a concentration of 0.50 g / l has a value of ESDD with dissolved heavy pollutant levels (> 0.1 mg/cm2), while thevalue of NSDD categorized insoluble lowlevel pollutants. Maximum leakage current value obtained by GI. Makale 4.73mA, GI. Sungguminasa 4.47 mA, GI. Tello 4.60 mA, GI. Long Tallo 4.67 mA and GI. Pangkep 4.87 mA.